MENYUSUN ALBUM FOTO MENGGUNAKAN POWERPOINT - Harmastuti - (LPPM IST AKPRIND Yogyakarta, 2019)
Photo album is an documentation of an activity, in its compilation can be computer-based and made interesting like loading multimedia elements loading images, text, animation in the form of slide shows. One of the easy-to-use software is PowerPoint, this software can display images, products or multimedia-based learning outcomes. On this occasion the introduction of PowerPoint software will be introduced, using the available facilities can be used to compile presentation materials, photo albums, multimedia-based creations. Together with the students of the Children's Foundation the Child Development Center (PPA) of Macedonia the Yogyakarta Student Center Bantul was introduced to how the preparation of the presentations contained photographs. Or known by composing a photo album using the facilities available in PowerPoint and introducing how to insert transitions, animations, sounds in the album created. As a result of the activity, students are motivated to compile interesting photo albums, are morefamiliar with PowerPoint software and can develop multimedia-based.